Failure Analysis of Solder Joint on A Single Sided Printed Circuit Board (PCB) - Mat Ayob, Mohd Adam; Embong, Zaidi (Enhanced Knowledge in Sciences and Technology, 2023)
This study mainly to investigate about either different concentration of corrosion agent could affect the reliability of the single-sided printed circuit board. Hence, the objectives of this study were to to investigate the voltage, current and resistance that lead to the failure of a corrosion product on a single-sided printed circuit board (PCB), to conduct corrosion experiment for PCBs solder joint using various sodium chloride (NaCl) concentration (0.5M, 1.0M, 2.0M) and to compare the value of voltage, current and resistance for pre and post corrosion test. Overall, on a single-sided printed circuit board, the failure analysis of a corrosion product (solder) actually takes place. Corrosion can cause the malfunction of the microelectronics components due to the higher likelihood and factors that can cause the printed circuit board to corrode easily. For some good recommendation, would recommend to have a longer immersion time and also a higher concentration of corrosion agent. A longer period of immersion test, would shows a greater effect on the printed circuit board especially on the solder joint while a higher concentration of corrosion agent solution will show an effectiveness of rapid rusting.